Volume 10: Ocean Renewable Energy 2017
DOI: 10.1115/omae2017-61512
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Offshore Three-Bladed Vertical Axis Wind Turbine for Wind Tunnel Experiments

Abstract: The rapid shrinkage of fossil fuel sources and contrary fast-growing energy needs of social, industrial and technological enhancements, necessitate the need of different approaches to exploit the various renewable energy sources. Among the several technological alternatives, wind energy is one of the most emerging prospective because of its renewable, sustainable and environment friendly nature, especially at its offshore locations. The recent growth of the offshore wind energy market has significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
(13 reference statements)
0
7
0
1
Order By: Relevance
“…Did not study the TSR and pitch angle effect. Aerodynamic performance enhancements of H-rotor Darrieus wind turbine [9] Used S1046 airfoil and introduced wind-lens to improve the performance. Studied various shapes but did not present any comparison with NACA series and did not study the TSR, solidity and pitch angle effect.…”
Section: Paper Titlementioning
confidence: 99%
See 1 more Smart Citation
“…Did not study the TSR and pitch angle effect. Aerodynamic performance enhancements of H-rotor Darrieus wind turbine [9] Used S1046 airfoil and introduced wind-lens to improve the performance. Studied various shapes but did not present any comparison with NACA series and did not study the TSR, solidity and pitch angle effect.…”
Section: Paper Titlementioning
confidence: 99%
“…The literature available on the simulation of H-Darrius VAWT performance primarily focused on finding the relative velocities and angle of attacks at different tip speed ratios and azimuthal positions, calculation of the ratio of induced to freestream velocity, methods of calculating the normal and tangential forces etc [9][10][11][12]. Besides, only few studies were conducted on VAWTs utilising S-series aerofoils at various pitch angles.…”
Section: Introductionmentioning
confidence: 99%
“… The angle of attack (α), defined as the angle between the blade chord and the resultant fluid velocity vector, is given by Eq. (6) [ 19 ]. where, is the azimuth angle presented in Figure 1 .…”
Section: Operational Parameters Of the Modelmentioning
confidence: 99%
“…Darrieus wind turbine designs were first patented in 1931 (Darrieus 1931). Many researchers studied the effects of design parameters on wind turbine performance (Delafin et al, 2016;Roy et al, 2017). Delafin et al, (2016) studied the effect of number of blades and solidity of VAWT on the power coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Hara, Hara, and Hayashi (2012) also concluded that with an increase in moment of inertia of the Darrieus wind turbine, the self-starting problem becomes more sever. Experiments in the wind tunnel showed that at high of the rotor, the Darrieus wind turbine with low blade solidity could generate more power, but at lower , the high solidity wind turbine had greater Cp (Roy et al, 2017). The analytical study of straight-blade design of VAWT for asymmetric blade showed that the increment of Height/Diameter (H/D) of wind turbine increased the mass per height unit material, which in turn led to increased blade solidity and manufacturing costs (Islam et al, 2011).…”
Section: Introductionmentioning
confidence: 99%